Relationship between thrombocytopenia and prognosis in children with septic shock: a retrospective cohort study - Ruichen Zhang; Haixin Huang; Siwei Lu; Jian Chen; Dandan Pi; Hongxing Dang; Chengjun Liu; Feng Xu; Yue-Qiang Fu (Platelets)
Septic shock is a life-threatening disease worldwide often associated with thrombocytopenia. Platelets play a crucial role in bridging the gap between immunity, coagulation, and endothelial cell activation, potentially influencing the course of the disease. However, there are few studies specifically evaluating the impact of thrombocytopenia on the prognosis of pediatric patients. Therefore, the study investigates effects of early thrombocytopenia in the prognosis of children with septic shock. Pediatric patients with septic shock from 2015 to 2022 were included monocentrically. Thrombocytopenia was defined as a platelet count of <100 × 109/L during the first 24 hours of septic shock onset. The primary outcome was the 28-day mortality. Propensity score matching was used to pair patients with different platelet counts on admission but comparable disease severity. A total of 419 pediatric patients were included in the analysis. Patients with thrombocytopenia had higher 28-day mortality (55.5% vs. 38.7%, p = .005) compared to patients with no thrombocytopenia. Thrombocytopenia was associated with reduced 28-PICU free days (median value, 0 vs. 13 days, p = .003) and 28-ventilator-free (median value, 0 vs. 19 days, p = .001) days. Among thrombocytopenia patients, those with platelet count ≤50 × 109/L had a higher 28-day mortality rate (63.6% vs. 45%, p = .02). Multiple logistic regression showed that elevated lactate (adjusted odds ratio (OR) = 1.11; 95% confidence interval (CI): 1.04–1.17; P <0.001) and white blood cell (WBC) count (OR = 0.97; 95% CI: 0.95–0.99; p = .003) were independent risk factors for the development of thrombocytopenia. Thrombocytopenia group had increased bleeding events, blood product transfusions, and development of organ failure. In Kaplan-Meier survival estimates, survival probabilities at 28 days were greater in patients without thrombocytopenia (p value from the log-rank test, p = .004). There were no significant differences in the type of pathogenic microorganisms and the site of infection between patients with and without thrombocytopenia. In conclusion, thrombocytopenia within 24 hours of shock onset is associated with an increased risk of 28-day mortality in pediatric patients with septic shock.